Deformation behaviour of ion-irradiated FeCr: a nanoindentation study - Song, K; Yu, H; Karamched, P; Mizohata, K; Armstrong, DEJ; Hofmann, F (Springer, 2022)
Understanding the mechanisms of plasticity in structural steels is essential for the operation of next-generation fusion reactors. This work on the deformation behaviour of FeCr, focusses on distinguishing the nucleation of dislocations to initiate plasticity, from their propagation through the material. Fe3Cr, Fe5Cr, and Fe10Cr were irradiated with 20 MeV Fe3+ ions at room temperature to doses of 0.008 dpa and 0.08 dpa. Nanoindentation was then carried out with Berkovich and spherical indenter tips. Our results show that the nucleation of dislocations is mainly from pre-existing sources, which are not significantly affected by the presence of irradiation defects or Cr%. Yield strength, an indicator of dislocation mobility, increases with irradiation damage and Cr content, while work hardening capacity decreases mainly due to irradiation defects. The synergistic effects of Cr and irradiation damage in FeCr appear to be more important for the propagation of dislocations than for their nucleation.